Detection of an Alphacoronavirus in a Brazilian Bat (Molossus sp.) - Molina, Cesar L. (2025)
Due to the COVID-19 pandemic and the uncertainty about aspects of its origin, in recent years there has been an increased interest in investigating coronaviruses in wild animals. Bats are hosts of the greatest diversity of coronaviruses to date, including the ancestors of viruses that have caused outbreaks in humans. Although in Brazil, information on coronaviruses in bats has expanded, still they remain unrepresentative. To help shed some light on this matter, we collected 175 samples from bats of different species from two Brazilian states. Here, we report the previously unknown presence of an alphacoronavirus in a bat (Molossus sp.) from Ceará. The phylogenetic analysis showed close relationships with alphacoronaviruses from Brazil and Argentina, but it was not possible to determine the subgenus or species of this virus using RNA-dependent RNA-polymerase (RdRp) domain of the nsp12 protein-coding sequence as it was distant from the specimens considered by the International Committee on Taxonomy of Viruses (ICTV). Finally, by performing High-Throughput Sequencing, we were able to find contigs mostly belonging to domains of the replicase of bat coronaviruses related to American bats of the Molossidae and Vespertilionidae families.